Talk on application of biotechnology in the process industries by Prof. Dr. Mohd Ali Hassan, Universiti Putra Malaysia - Tan, Jennifer Yee Ying (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/